184 Years Not Out: a Brief history of the Library of the Law Society of England and Wales. (16th March 2016) - Maher, Michael
Abstract: In this article Michael Maher, Librarian of the Law Society of England and Wales, examines the history of the extensive library on Chancery Lane, the range of services it provides to help support its members (including their agents i.e. law librarians) and the future plans for the library.